An experimental evaluation of engine performance and emisssion characteristics of CI engine operated with Roselle and Karanja biodiesel. (15th October 2019) - Shrivastava, Pankaj; Verma, Tikendra Nath; Pugazhendhi, Arivalagan
Highlights: Characteristics of Roselle and Karanja biodiesel are studied and compared it with diesel. Blend LA20 and KB20 perform better engine performance than with other biodiesel blends. Shows the tremendous potential to decrease CO2 emission with increasing engine load. Biodiesels fuel emits lower NOx and smoke emission than with diesel fuel. BSFC for biodiesel and its blends were higher compared to diesel fuel. Abstract: The increasing population growth is demanding alternative fuels with the fast depletion of world fossil fuel reserves. In this research work, biodiesel was produced from Roselle and Karanja oil by using the transesterification process. Different blends of Roselle and Karanja biodiesels were prepared and their effects were examined experimentally with different engine loads (low, medium and full load) at constant engine speed. Experimental studies showed reductions in brake thermal efficiency, exhaust gas temperature, indicated thermal efficiency, maximum rate of pressure rise rate and ignition delay by 4.3, 1.2, 0.71, 4.93 and 2.47%, respectively for LA20 (20% Roselle + 80% diesel) as compared to diesel. The results also showed reductions in NOx emission by 6.01% and smoke emission by 12.59% while there was an improvement in brake specific fuel consumption by 6.84% and carbon dioxide emission by 3.73%, respectively for LA20. KB20 (20% Karanja + 80% diesel) showed reduced brake thermal efficiency, exhaust gas temperature, NOx and smoke emissions by 1.82, 1.64, 3.83 and 13.63%, respectively while showing increased brake specific fuel consumption upto 8.5%. Thus, LA20 and KB20 seem to be the most potential alternative fuels for diesel engine.